Monitoring system for the charging and discharging station of electric vehicles (EVs) - Zou, Lei (2014)
Electric Vehicles are being adopted widely throughout the recent years due to the clean energy and sustainability concerns. With the concept of “Valley Filling and Peak Shaving”, more advantages are added into Electric Vehicles. It can help to stabilize the electric power grid during high load and low load period, thus it much profit to the current power grid infrastructure. This project aims to demonstrate this concept by building up a battery charging station mock-up to provide large flexibility for operating based on the concept.